Differential responses from the left postcentral gyrus, right middle frontal gyrus, and precuneus to meal ingestion in patients with functional dyspepsia - Chen, Yiping; Yu, Risheng; DeSouza, Joseph F. X.; Shen, Yuze; Zhang, Hanyun; Zhu, Chunpeng; Huang, Peiyu; Wang, Caihua (Frontiers in Psychiatry, 2023)
Background: Functional dyspepsia (FD) is most often a meal-induced syndrome, studies using resting-state functional magnetic resonance imaging (rs-fMRI) reported abnormal connectivity in areas related to pain processing in FD. But few studies have set out to determine how meal ingestion affects the brain working patterns, Through rs-fMRI, this study observed how meal ingestion affected brain regions related to visceral hypersensitivity and emotional response networks in FD. Methods: 30 FD patients and 32 healthy controls (HC) were enrolled and underwent clinical investigations, rs-fMRI were performed twice after a 4-hour fast and 50-minute after meal, the mean functional connectivity strength (FCS) values were extracted from brain regions with significant differences to show the trend of changes related to meal ingestion after FCS analyses, Results: Depression, anxiety, sleep disturbances, and weight loss were more common in FD patients (P≤0.001). Compared with HCs (corrected cluster P value < 0.05), FD patients had significantly higher FCS in the right middle frontal gyrus before meals and higher meal-induced FCS in the left postcentral gyrus. HCs had greater meal-induced activation in the right precuneus and anterior cingulate cortex, and FD had a decreasing trend in the right inferior frontal gyrus compared to the increasing trend in HCs. We only found anxiety was negatively correlated with FCS in the right inferior frontal gyrus in FD (r=-0.459，p=0.048, uncorrected). Conclusions: Here we showed FD patients have different perceptual and emotional responses to food intake in defined brain area, providing promising impetus for understanding brain pathogenic mechanism in FD.